2019
DOI: 10.1002/ptr.6285
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive effects of the standardized extract of Zingiber zerumbet on innate immune responses in Wistar rats

Abstract: Zingiber zerumbet rhizome has been used in traditional medicine mainly for the treatment of various immune-inflammatory related ailments and has been shown to exhibit a wide spectrum of biological effects especially antioxidant and anti-inflammatory activities. The present study was aimed to investigate the immunosuppressive effects of the standardized 80% ethanol extract of Z. zerumbet at 100, 200, and 400 mg/kg on the innate immune responses in male Wistar rats. The immune parameters determined were chemotax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Antioxidant enzymes, such as SOD and GSH-Px plus GSH, which are scavengers of ROS in the liver, are the first line of defense against oxidative stress-induced tissue injury [34]. Several previous studies have shown that ZER can inhibit the generation of ROS [35,36,37,38]. For instance, ZER was found to provide protection to pancreatic β cells from high glucose-induced cytotoxicity through directly interfering with ROS production [39].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant enzymes, such as SOD and GSH-Px plus GSH, which are scavengers of ROS in the liver, are the first line of defense against oxidative stress-induced tissue injury [34]. Several previous studies have shown that ZER can inhibit the generation of ROS [35,36,37,38]. For instance, ZER was found to provide protection to pancreatic β cells from high glucose-induced cytotoxicity through directly interfering with ROS production [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, between the diterpene compounds that have been isolated from the extract, andrographolide (1), 14-deoxyandrographolide (2), and 14-deoxy-11,12-didehydroandrographolide (3), only 1 significantly inhibited the proliferation of cancer cells with GI 50 (concentration required to inhibit the 50% growth) values between 10 and 28 µM [29]. Among active terpenes, zerumbone (4, Figure 2), a sesquiterpenoidic derivative found in the rhizomes of Zingiberaceae plants, showed different pharmacological properties like antioxidant, antibacterial, antipyretic, anti-inflammatory, immunomodulatory, as well as anti-neoplastic [30,31]. This compound exerted its antitumor activity significantly suppressing expansion and metastasis by modulating nuclear factor kappa of activated B Among active terpenes, zerumbone (4, Figure 2), a sesquiterpenoidic derivative found in the rhizomes of Zingiberaceae plants, showed different pharmacological properties like antioxidant, antibacterial, antipyretic, anti-inflammatory, immunomodulatory, as well as anti-neoplastic [30,31].…”
Section: Terpenesmentioning
confidence: 99%
“…Among active terpenes, zerumbone (4, Figure 2), a sesquiterpenoidic derivative found in the rhizomes of Zingiberaceae plants, showed different pharmacological properties like antioxidant, antibacterial, antipyretic, anti-inflammatory, immunomodulatory, as well as anti-neoplastic [30,31]. This compound exerted its antitumor activity significantly suppressing expansion and metastasis by modulating nuclear factor kappa of activated B Among active terpenes, zerumbone (4, Figure 2), a sesquiterpenoidic derivative found in the rhizomes of Zingiberaceae plants, showed different pharmacological properties like antioxidant, antibacterial, antipyretic, anti-inflammatory, immunomodulatory, as well as anti-neoplastic [30,31]. This compound exerted its antitumor activity significantly suppressing expansion and metastasis by modulating nuclear factor kappa of activated B cells (NF-kB), protein kinase B (PKB), interleukin 6/janus kinase 2/signal transducer, activator of transcription 3 (IL-6/JAK2/STAT3), and their downstream target proteins.…”
Section: Terpenesmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo Male wistar rats ZER inhibited the migration of neutrophils, expressions of CD11b/CD18 integrin, phagocytic activity, and production of reactive oxygen species [162] In vitro CD18 integrin expression and phagocytic engulfment ZER showed strong inhibition on the phagocytosis of neutrophils.Z [163] In vitro Asthmatic mouse model ZER reduced ovalbumin (OVA)-specific immunoglobulin E (IgE) and induced IgG2a antibody production. It also reduced the production of eotaxin, keratinocyte-derived chemokine (KC), IL-4, IL-5, IL-10, and IL-13, and promoted Th1 cytokine interferon (IFN)-γ production.…”
Section: Immunosuppressive and Immunomodulatory Activitiesmentioning
confidence: 88%